2018
DOI: 10.1590/0103-8478cr20170505
|View full text |Cite
|
Sign up to set email alerts
|

Skin antisepsis protocols for the collection of blood from donor dogs

Abstract: The objective of this study was to evaluate and compare the bactericidal efficacy of2% chlorhexidine surfactant solution + 70% alcohol and 2% chlorhexidine surfactant solution + 0.5% chlorhexidine-alcohol, and standardize skin antisepsis for blood collection from donor dogs. One hundred and twenty skin swabsof the jugular regions of 20 dogs were evaluated. Swabs were distributed into six treatment(T) groups according to the disinfectant used and removal or retention of local hair: T1involved neither antisepsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The results showed that there was no significant difference between the use of 0.5% alcoholic CHG and 2% dehydrating CHG, as both reduced the UFC count by 100% 3 min after use and maintained residual action until the end of the surgical procedure. This result was similar to other studies where CHG was used in the antisepsis of dogs and cats (Osuna et al, 1990;Silva et al, 2000;Marchi et al, 2018). Alcoholic CHG 0.5% is easier and more practical to apply to the skin, with no need to remove the excess product, as it evaporates, leaving the skin dry, unlike what happens with CHG degermante, where it is necessary to remove the excess product.…”
Section: Bacterial Countsupporting
confidence: 88%
“…The results showed that there was no significant difference between the use of 0.5% alcoholic CHG and 2% dehydrating CHG, as both reduced the UFC count by 100% 3 min after use and maintained residual action until the end of the surgical procedure. This result was similar to other studies where CHG was used in the antisepsis of dogs and cats (Osuna et al, 1990;Silva et al, 2000;Marchi et al, 2018). Alcoholic CHG 0.5% is easier and more practical to apply to the skin, with no need to remove the excess product, as it evaporates, leaving the skin dry, unlike what happens with CHG degermante, where it is necessary to remove the excess product.…”
Section: Bacterial Countsupporting
confidence: 88%
“…Immediately after the pain reflex became absent, a trichotomy was performed with sterile razor blades and degermation using chlorhexidine degermant solution and 2% alcoholic chlorhexidine (Rioquímica, São José do Rio Preto, SP, Brasil) solution. Next, cloth from previously sterilized fields was used to delimit and isolate the surgical area [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…From each animal 15ml/kg of blood was sampled and placed in two 450 mL plastic bags: citrate phosphate dextrose-adenine: CPDA-1 bag (Fresenius Hemocare ® , Fresenius Kabi Brazil Ltda., Barueri, SP, Brazil), and citrate phosphate dextrose with saline glucose mannitol: CPD/SAG-M bag (Fresenius Hemocare ® , Fresenius Kabi Brazil Ltda., Barueri, SP, Brazil). Prior to collection, the puncture area over the jugular vein was shaved and aseptically prepared (MARCHI et al, 2018). Both samples were collected simultaneously by external jugular vein venipuncture; they were homogenized and weighed using a digital scale (Model BN, Coimma ® Farming Ltd, Dracena, SP, Brazil).…”
Section: Methodsmentioning
confidence: 99%